2005
DOI: 10.1136/bmj.38441.620417.8f
|View full text |Cite|
|
Sign up to set email alerts
|

Randomised controlled trial to compare surgical stabilisation of the lumbar spine with an intensive rehabilitation programme for patients with chronic low back pain: the MRC spine stabilisation trial

Abstract: Objectives To assess the clinical effectiveness of surgical stabilisation (spinal fusion) compared with intensive rehabilitation for patients with chronic low back pain. Design Multicentre randomised controlled trial. Setting 15 secondary care orthopaedic and rehabilitation centres across the United Kingdom. Participants 349 participants aged 18-55 with chronic low back pain of at least one year's duration who were considered candidates for spinal fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
258
2
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 458 publications
(278 citation statements)
references
References 23 publications
11
258
2
7
Order By: Relevance
“…26 Chronic low back pain in 349 patients aged 18-55 years found no evidence that surgery was any more beneficial than intensive rehabilitation. 27 A study of 600 single-operated low back patients showed that 71% did not return to work 4 years after surgery, and 400 multiple-operated backs showed that 95% did not return to work 4 years later. 28 Treating lumbar disk herniation and spinal stenosis patients successfully with conservative care is documented.…”
Section: Discussionmentioning
confidence: 99%
“…26 Chronic low back pain in 349 patients aged 18-55 years found no evidence that surgery was any more beneficial than intensive rehabilitation. 27 A study of 600 single-operated low back patients showed that 71% did not return to work 4 years after surgery, and 400 multiple-operated backs showed that 95% did not return to work 4 years later. 28 Treating lumbar disk herniation and spinal stenosis patients successfully with conservative care is documented.…”
Section: Discussionmentioning
confidence: 99%
“…The goal of a fusion of the lumbar spine is to obtain a primary solid arthrodesis so as to alleviate pain [10,11,14,15,19,22,31]. Different circumferential or ''360°'' fusion techniques have been described such as combined anteriorposterior fusion (APF), instrumented posterior lumbar interbody fusion (PLIF) and transforaminal lumbar interbody fusion (TLIF).…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have seen a significant rise in the number of lumbar spinal fusion (LSF) procedures, but only few studies have reviewed different rehabilitation strategies after LSF [1][2][3][4][5]. A study published in 2003 compared the effect of three different postoperative rehabilitation programs initiated 3 months after LSF.…”
Section: Introductionmentioning
confidence: 99%